Strategi Pengembangan Agroindustri Santan Kelapa - Meilizar Meilizar; Rika Ampuh Hadiguna; Santosa Santosa; Nofialdi Nofialdi (Jurnal Sosial Ekonomi Pertanian, 2023)
Coconut is a superior product and is widely cultivated in the Padang Pariaman Region. The progress of the coconut agroindustry is predicted to have the ability to increase farmer motivation and coconut cultivation efficiency, thus stimulating the expansion of rural industries. The research aims to formulate a coconut milk agroindustry development strategy that is designed with a systems approach through the integration of coconut farming sub-systems and coconut processing sub-systems to maximize coconut farming profits and ensure the fulfillment of coconut milk agroindustry production capacity to support local food product industries. This research seeks to carry out a series of stages involving coconut farmers and coconut milk agroindustry players in Padang Pariaman, completing questionnaires by experts, SWOT analysis to identify and calculate the IFE and EFE weights of coconut milk agroindustry, and identification of strategies for developing coconut milk agroindustry through the application of AHP. Based on the research results, it was found that the coconut milk agroindustry development strategy through horizontal integration by establishing a coconut milk agroindustry that is integrated with farmers as suppliers of coconut granules to meet the demand for a supply of quality coconut milk for the local food product industry can be realized.